2021
DOI: 10.1002/1873-3468.14063
|View full text |Cite
|
Sign up to set email alerts
|

The 14‐3‐3 protein YWHAB inhibits glucagon‐induced hepatic gluconeogenesis through interacting with the glucagon receptor and FOXO1

Abstract: Glucagon antagonism has been reported as a new therapeutic approach to hyperglycaemia. As the 14‐3‐3 protein YWHAB has been identified as a regulator of the glucagon receptor (GCGR) by affinity purification and mass spectrometry, we examined the role of YWHAB in vivo. Ywhab knockout mice display impaired blood glucose homeostasis only under pyruvate stimulation. Deletion of Ywhab in mouse primary hepatocytes (MPHs) increases hepatocyte glucose production by magnifying the effect of glucagon. Mechanistic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…YWHAB (14-3-3 protein beta, also known as tyrosine 3-monooxygenase/tryptophan 5monooxygenase activation protein, beta polypeptide) is one of seven isoforms comprising the 14-3-3 proteins. Several studies have shown that YWHAB mediates some obesity-related metabolic pathways, such as insulin signaling, PI3K-AKT-FoxO1 signaling and AMPK signaling, by regulating the activity of its key regulators [47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…YWHAB (14-3-3 protein beta, also known as tyrosine 3-monooxygenase/tryptophan 5monooxygenase activation protein, beta polypeptide) is one of seven isoforms comprising the 14-3-3 proteins. Several studies have shown that YWHAB mediates some obesity-related metabolic pathways, such as insulin signaling, PI3K-AKT-FoxO1 signaling and AMPK signaling, by regulating the activity of its key regulators [47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…YWHAB is a signaling protein that regulates the glucagon receptor and the loss of Ywhab in mice impaired glucose homeostasis. 49,50 Taken together, the sQTL and exon eQTL, which use different RNA-seq reads, provide stronger evidence of splicing events that correspond to GWAS signals.…”
Section: Colocalization Of Sqtls and Cardiometabolic Gwas Locimentioning
confidence: 99%